Chinese Medicine Combined With EGFR-TKIs Prolongs Progression-Free Survival and Overall Survival of Non-small Cell Lung Cancer (NSCLC) Patients Harboring EGFR Mutations, Compared With the Use of TKIs Alone - Wang, Yujia; Wu, Guoyu; Li, Ru; Luo, Yingzhe; Huang, Xingmei; He, Lifang; Zhong, Huihui; Xiong, Shaoquan (Frontiers in Public Health, 2021)
Objective: To explore the efficacy comparison between epidermal growth factor receptor–tyrosine kinase inhibitors (EGFR-TKIs) combined with traditional Chinese medicine (TCM) and single EGFR-TKIs for advanced non-small cell lung cancer (NSCLC). Methods: A total of 91 NSCLC patients with EGFR mutation were divided into an experimental group and a control group (in a ratio of 2:1) to receive TCM and EGFR-TKIs (61 cases) or single EGFR-TKIs (30 cases). Patients in the control group took EGFR-TKIs and those in the experimental group took EGFR-TKIs plus TCM. We analyzed the progression-free survival (PFS), overall survival (OS), disease control rate (DCR), and treatment-related adverse events of two groups. Results: The mPFS of the experimental group and the control group was 12.3 and 8.9 months (P = 0.02), respectively, and the mOS of the experimental group and the control group was 28.2 and 24.2 months (P = 0.02), respectively. Subgroup analysis showed that for the patients with exon 19 deletion mutation (19DEL), mPFS between experimental group and control group was 12.7 and 10.1 months, respectively (P = 0.12). For exon 21 deletion mutation (L858R), the PFS of two groups was 10.8 vs. 8.2 months, respectively (P = 0.03). The subgroup analysis also showed that, for the patients with exon 19 deletion mutation, mOS between the experimental group and the control group was 30.3 and 28.7 months, respectively (P = 0.19). For exon 21 deletion mutation, the mOS of two groups was 25.5 vs. 21.3 months, respectively (P = 0.01). The DCR of the experimental group and the control group was 93.3% and 80.1%, respectively (P = 0.77). Grade 3–4 treatment-related adverse events were less common with the experimental group (11.48%) than the control group (26.67%). Conclusion: For NSCLC patients with EGFR mutation, EGFR-TKIs combined with TCM had a certain effect to prolong mPFS and mOS, compared with the use of EGFR-TKIs alone, especially for the patients with L858R. This conclusion has a significant effect on improving the survival of NSCLC patients after EGFR-TKIs resistance. It deserves further study.